TEENAGE SUBCULTURE: PSYCHOLOGICAL AND SOCIO GROUP FEATURES - Hryshchuk, Yuliya V. (Educological discourse, 2014)
In the article analyzes the basic psychological and socio group features members of teenage subcultures. The system of values teenagers who are members of subcultures and characteristic changes in their behavior. Characterized specificity of formation of teenage subcultures; defined features of teenage subcultures at leisure fulfillment. The author emphasizes that social and psychological characteristics of members of teenage subcultures depend not only on their relation in the middle of the subculture, but also on attitudes of society.